Activation of the ARCPOMC→MeA Projection Reduces Food Intake - Kwon, Eunjin; Jo, Young-Hwan (Frontiers in Neural Circuits, 2020)
Proopiomelanocortin (POMC) neurons in the arcuate nucleus of the hypothalamus (ARC) plays an essential role in the control of food intake and energy expenditure. Melanocortin-4 receptors (MC4Rs) are expressed in key areas that are implicated in regulating energy homeostasis. Although the importance of MC4Rs in the paraventricular hypothalamus (PVH) has been well documented, the role of MC4Rs in the medial amygdala (MeA) on feeding remains controversial. In this study, we specifically examine the role of a novel ARCPOMC->MeA neural circuit in the regulation of short-term food intake. To map a local melanocortinergic neural circuit, we use monosynaptic anterograde as well as retrograde viral tracers and perform double immunohistochemistry to determine the identity of the neurons receiving synaptic input from POMC neurons in the ARC. To investigate the role of the ARCPOMC->MeA projection on feeding, we optogenetically stimulate channelrhodopsin-2 (ChR2)-expressing POMC fibers in the MeA. Anterograde viral tracing studies reveal that ARC POMC neurons send axonal projections to estrogen receptor- (ER-)- and MC4R-expressing neurons in the MeA. Retrograde viral tracing experiments show that the neurons projecting to the MeA are located mainly in the lateral part of the ARC. Optogenetic stimulation of the ARCPOMC->MeA pathway reduces short-term food intake. This anorectic effect is blocked by treatment with the MC4R antagonist SHU9119. In addition to the melanocortinergic local circuits within the hypothalamus, this extrahypothalamic ARCPOMC->MeA neural circuit would play a role in regulating short-term food intake.